HUMANITARIAN INTERVENTION FROM COLD WAR ERA TO THE PRESENT: NEO-REALIST PERSPECTIVE - Hasan Fatih Seval (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The goal of this study is toanalyze the 'humanitarian intervention' from the neo-realist perspective. Inthe first part of this article, the basic concepts and principles of theneo-realist theory, one of the main theories of international relations discipline,will be addressed. In the second part of the article, the concept ofhumanitarian intervention will be defined and a review will be conducted on theimplementations of the theory, and the execution of humanitarian intervention. Mainquestions of the article are as following: how the "humanitarian"aspect of the Cold War's neo-realist nature was perceived and how it changedand developed in the post-Cold War era; what is the main implications ofneo-realist theory for the 'humanitarian' world; and how the neo-realist perceptionaffected the 'humanitarian intervention'.